Anxiety symptoms, sleep disturbance, and academic achievement among Afghan female school students: A cross-sectional study - Ahmad Neyazi; Bilal Ahmad Rahimi; Abdul Qadim Mohammadi; Nosaibah Razaqi; Laila Qanawezi; Shaharah Sarem; Saida Said; Raz Mohammad Tabib; Habibah Afzali; Mehrab Neyazi; Mark D. Griffiths (Sleep Epidemiology)
Background: Anxiety is a common psychological disorder in school-aged children and adolescents. The present study aimed to assess the prevalence of anxiety symptoms and sleep disturbances and their relationship with academic achievement among female students in Herat, Afghanistan. Methods: A cross-sectional survey of 737 female students (mean age 11.8 years old) was conducted across 10 randomly selected schools in Herat, Afghanistan, covering Grades 1 to 6. Students were randomly chosen within these schools. The Depression Anxiety Stress Scale for Youth (DASS-Y) and Pittsburgh Sleep Quality Index (PSQI) assessed anxiety and sleep disturbance, while academic achievement ratings were provided by schoolteachers. Results: Using the DASS-Y and the PSQI, 65.5% reported anxiety symptoms and 46.4% reported sleep disturbance. Low academic achievement correlated significantly with anxiety (r = 0.228) and sleep issues (r = 0.161). Multiple logistic regression analysis identified predictors for anxiety and sleep disturbance. Predictors for anxiety included being aged 13–16 years, having lower class grade, being of low economic status, and having unemployed parents. Predictors for sleep disturbance included being aged 13–16 years, having lower class grade, having an uneducated father, being of low economic status, and having unemployed parents. Conclusion: There is a high prevalence of anxiety symptoms and sleep disturbances among female school students in Herat, Afghanistan. Significant correlations exist between students' academic achievement, anxiety, and sleep disturbances. Addressing anxiety and sleep disturbances among Afghan female school students could be facilitated by revising current government policies concerning students' health. Educational campaigns focused on sleep hygiene and anxiety management for both students and their parents may also prove beneficial.